ANALISIS YURIDIS ATAS TUNTUTAN SUAMI TERHADAP HARTA BAWAAN ISTRI YANG DIPEROLEH SEMASA PERKAWINAN (STUDI KASUS PERKARA PERDATA NO.146/Pdt.G/2014/PN.Dps) - YENITA MARTHA PANDIANGAN (PREMISE LAW JURNAL, 2016)
In public opinion, joint property is the property which is obtained by a married couple so that when there is a divorce there will be the claim on it by both of them. If there is no agreement before a marriage occurs and a divorce takes place, there will be a dispute on it between husband and wife. In this case, each of the couple claims that the property is his or hers. Each of them (the widower or the widow) thinks that he or she has the right on the joint property. The legal provision on the property (land and building) given by the wife’s parents during the case of marriage when there is a divorce in which the husband claims that it is a joint property. It also analyzes legal protection for the ex-husband who claims that he has the right on the property given by his wife’s parents during their marriage.The result of the research showed that in the Marriage Law, there is no detailed explanation on joint property and pre-marital property. In the case of joint property in which each of the married couple thinks that the disputed property does not belong to joint property is determined by the capacity and the success of the plaintiff and the defendant in proving that the disputed property has been obtained during the marriage whether the money which has been used to buy it comes from his or her own effort or it comes from their mutual effort. Keywords: Claim, Pre-marital property